Damage induced by recycled Construction and Demolition Wastes on the short-term tensile behaviour of two geosynthetics - Castorina Silva Vieira (2015)
Geosynthetics have been used as a reinforcement material in roadways and railways construction. Notwithstanding, one of the main questions of using is their durability. The damage caused by the mechanical actions during installation and the chemical and biological degradation are important issues to consider in the physical, mechanical and hydraulic behaviour of geosynthetics. The change in their properties induced by these degradation processes can compromise the performance of these materials. In order to study the chemical and environmental degradation induced by a recycled Construction and Demolition Waste (C&DW) on the short-term tensile behaviour of two geosynthetics (a uniaxial HDPE geogrid and a nonwoven PP geotextile reinforced with PET yarns) used commonly as reinforcement material, a damage trial embankment (2 m x 3 m in plan) was constructed. This paper presents and discusses the effects produced by the recycled C&DW on geosynthetic samples exhumed after 6 months of the embankment construction. The constituents and the leaching behaviour of the recycled C&DW are presented. Wide width tensile tests were performed on exhumed and intact (as-received) geosynthetics and their tensile behaviour is compared. Scanning electron microscope (SEM) images of intact and exhumed specimens are also presented. As expected the degradation induced by the recycled C&DW after 6 months of exposure is not very expressive. On the HDPE geogrid the recycled C&DW induced a small decrease on the tensile strength and the reduction of the tensile stiffness modulus. The geocomposite experienced some reduction on the tensile strength (16% on average) but the effects on tensile stiffness and shape of the load-strain curves were not significant.